Pengaruh Komunikasi, Kerjasama Tim Dan Reward Terhadap Kinerja Karyawan Mcdonald’s Sri Ratu Kediri - Erika Novya Lestari; Moch. Saleh Udin; Taufik Akbar (Universitas Kristen Indonesia Toraja, 2023)
This research is motivated by the fact that in a public company operating in the fast food sector, human resources are very important in achieving company goals. The aim of this research is to explain the influence of communication, teamwork and rewards on employee performance. This research method uses a quantitative method using a questionnaire as data. This research uses a saturated sample method. The sample in this research was all 53 employees. The technique used to analyze the data is the SPSS 25 program. The data analysis technique in this research is multiple linear regression analysis, coefficient of determination (R2), t test and F test. The results of this partial test (t) show that the communication variable has a significant value of 0.030 < 0.05, which means that the communication variable partially or significantly influences employee performance. The teamwork variable has a significant value of 0.045 <0.05, partially influencing or being significant on employee performance. The reward variable has a significant value of 0.901 > 0.05 and partially does not have a significant effect on employee performance. And the F test results show that the variables of communication, teamwork and rewards have a significant effect on employee performance with a significant value of 0.000 < 0.05. So it can be concluded that communication and teamwork partially have a significant effect on employee performance, while rewards do not have a significant effect on employee performance. And simultaneously these three variables have a significant effect on the performance of McDonald's Sri Ratu Kediri employees.